Penundaan Kewajiban Pembayaran Utang (PKPU) Dalam Hukum Kepailitan - Nugraha Budi Raharja; Ariawan Gunardi (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract In the era of globalization and growing economic dynamics, the problem of corporate bankruptcy is becoming an increasingly complex issue and requires a careful legal approach. Bankruptcy of a company not only has an impact on the business actor itself but also has a significant impact on related stakeholders, including creditors, employees and the wider community. Therefore, developing legal mechanisms that can manage the bankruptcy process efficiently and fairly is a must. The aim of this research is to understand the legal provisions governing the independence of PKPU management regarding company assets. The type of research method in this writing is qualitative with document type. Qualitative research is a type of research whose results are not based on statistical figures or other calculations. Article 234 paragraph (2) of the Bankruptcy and PKPU Law stipulates criminal/civil sanctions for PKPU administrators who are not independent, but without details, leaving room for interpretation by judges. The PKPU management plays a role in incoming/outgoing money, transferring assets, and approving debtor assets. The success of the PKPU management is determined by the working relationship with the company/debtor. In decomposing the debtor's assets, a detailed list and assessment of the value of the assets is carried out. The PKPU management must ensure that the actions of the company management are with their approval. The PKPU Application process involves a list of receivables/debts, in some cases the aim is peace or debt repayment, even bankruptcy. The effectiveness of PKPU debt settlement can be hampered by uncooperative debtors, hiding/selling assets, and creditors with bad intentions. The good faith of all parties is important so that the PKPU process runs smoothly. Keywords: PKPU, Bankruptcy, Company Assett Abstrak Dalam era globalisasi dan dinamika ekonomi yang terus berkembang, masalah kebangkrutan perusahaan menjadi isu yang semakin kompleks dan memerlukan pendekatan hukum yang cermat. Kepailitan suatu perusahaan tidak hanya berdampak pada pelaku usaha itu sendiri tetapi juga memberikan dampak signifikan pada stakeholder terkait, termasuk kreditur, karyawan, dan masyarakat luas. Oleh karena itu, pengembangan mekanisme hukum yang dapat mengelola proses kebangkrutan dengan efisien dan adil menjadi suatu keharusa. Tujuan dari penelitian ini adalah untuk memahami ketentuan hukum yang mengatur kemandirian pengurus PKPU terhadap harta kekayaan perusahaan. Jenis metode penelitian dalam penulisan ini ialah kualitatif dengan jenis dokumen. Penelitian kualitatif merupakan jenis penelitian yang hasilnya bukan didasarkan pada angka statistic atau perhitungan lainnya. Pasal 234 ayat (2) UU Kepailitan dan PKPU menetapkan sanksi pidana/perdata bagi pengurus PKPU yang tidak independen, namun tanpa rincian, memberi ruang interpretasi hakim. Pengurus PKPU berperan dalam pemasukan/pengeluaran uang, pengalihan harta, dan menyetujui perikatan harta debitor. Keberhasilan pengurus PKPU ditentukan hubungan kerja dengan perusahaan/debitor. Dalam penguraian harta debitor, daftar rinci dan penilaian nilai harta dilakukan. Pengurus PKPU harus memastikan tindakan pengurus perusahaan dengan persetujuannya. Proses PKPU Permohonan melibatkan daftar piutang/utang, dengan beberapa kasus tujuannya pada perdamaian atau pelunasan utang, bahkan kepailitan. Efektivitas penyelesaian utang PKPU bisa terhambat oleh debitor tidak kooperatif, penyembunyian/penjualan aset, dan kreditor beritikad buruk. Itikad baik semua pihak penting agar proses PKPU lancar. Kata Kunci: PKPU, Kepailitan, Harta Perusahaan